Photon scattering in geometrical optics - Waldenfels, Wilhelm von (Journal of mathematical physics, 2010)
A quasimonochromatic wave packet is scattered by a system of two level atoms. The transition frequency of atoms coincides with the frequency of the wave packet, their distances are proportional to that frequency. The time evolution can be calculated explicitly. Using Fourier-Weyl transform and after some renormalization, we establish the limit of geometrical optics. Applying the singular coupling limit, we arrive at the result: the main part of the wave packet is unperturbed, and the scattered part yields an intensity distribution in the six dimensional space of positions and wave numbers. This distribution contains all interferences. The Huygens-Fresnel theory yields an approximation of our result.
Published Online: 09 July 2010
Gesehen am 26.06.2018